Case of Ebstein Anomaly Complicated by Left Ventricular Outflow Tract Obstruction Secondary to Deformed Basal Septum Attributable to Atrialized Right Ventricle. Issue 4 (26th January 2016) - Hirata, Kazuhito; Yagi, Nobuhito; Kubota, Shuji; Wake, Minoru; Tengan, Toshiho
Abstract : Supplemental Digital Content is available in the text.